Hydatid fluid from Echinococcus granulosus induces autophagy in dendritic cells and promotes polyfunctional T-cell responses - Chop, Maia (2024)
Parasites possess remarkable abilities to evade andmanipulate the immune response of their hosts. Echinococcus granulosus is a parasitic tapeworm that causes cystic echinococcosis in animals and humans. The hydatid fluid released by the parasite is known to contain various immunomodulatory components that manipulate host´s defensemechanism. In this study,we focused on understanding the effect of hydatid fluid on dendritic cells and its impact on autophagy induction and subsequent T cell responses. Initially, we observed a marked downregulation of two C-type lectin receptors in the cell membrane, CLEC9A and CD205 and an increase in lysosomal activity, suggesting an active cellular response to hydatid fluid. Subsequently, we visualized ultrastructural changes in stimulated dendritic cells, revealing the presence of macroautophagy, characterized by the formation of autophagosomes, phagophores, and phagolysosomes in the cell cytoplasm. To further elucidate the underlying molecular mechanisms involved in hydatid fluid-induced autophagy, we analyzed the expression of autophagy-related genes in stimulated dendritic cells. Our results demonstrated a significant upregulation of beclin-1, atg16l1 and atg12, indicating the induction of autophagy machinery in response to hydatid fluid exposure. Additionally, using confocal microscopy, we observed an accumulation of LC3 in dendritic cell autophagosomes, confirming the activation of this catabolic pathway associated with antigen presentation. Finally, to evaluate the functional consequences of hydatid fluid-induced autophagy in DCs, we evaluated cytokine transcription in the splenocytes. Remarkably, a robust polyfunctional T cell response, with inhibition of Th2 profile, is characterized by an increase in the expression of il-6, il-10, il-12, tnf-a, ifn-g and tgf-b genes. These findings suggest that hydatid fluidinduced autophagy in dendritic cells plays a crucial role in shaping the subsequent T cell responses, which is important for a better understanding of host-parasite interactions in cystic echinococcosis.